A systematic analysis of molecular mechanisms in non-metastatic renal cancer delineates affected regulatory pathways and genes in tumor growth - Xia, Rongjun; Lin, Lijuan; Yu, Shengjin; Zhang, Jinhui; Zheng, Linlin; Zhou, Lijie; Lin, Junrong (Cellular and Molecular Biology, 2022)
In the recent century, Kidney cancer has emerged as one of the critical renal diseases. Therefore, we analyzed gene expression profiles of non-metastatic kidney cancer to find mechanisms associated with the early-stage pathogenesis of the disease. We concentrated on the most dysregulated genes in expression to discover possible unknown proliferative molecular mechanisms and oncogenic pathways promoting kidney renal cancer growth. Survival analysis, expression profiling, and gene set over-representation analysis were conducted on the most upregulated and most down-regulated genes alongside the hub genes. Our results demonstrated that pathways engaged in the metabolism of amino acids and carbohydrates and those involved in peroxisome organization were shown to be important in developing benign tumors. Furthermore, upregulation of genes such as CXCL9 and 10 genes and CXCR4 in chemokine response pathways would bolster differentiation and engagement of immune cells in the tumor microenvironment. C3, one of the essential members of the complement system, with a high degree and betweenness centrality in the PPI network, upregulated significantly not only in our analysis but also in the validation expression profiling results and survival analysis. We also identified genes such as TYROBP, ITGB2, and EGFR to be engaged in both immunological pathways and superoxide pathways. Furthermore, we found that downregulation of Aldolase B engaged in Glycolysis and Gluconeogenesis pathways would help develop benign tumors. Finally, many top hub genes, including TYMS, PTPRC, AURKA, FN1, UBE2C, and CD53 were proposed to be engaged in the progression of non-metastatic renal tumors. This holistic interrogation calls attention to investigate further and experimentally validate the proposed molecular mechanisms.